The Problem of Social and Professional Adaptation of University Graduates in Higher Education Development - Druzhinina, Vera; Shubina, Natalia; Akinina, Natalia; Lazutkina, Olesya (Journal of History Culture and Art Research, 2018)
Some problems of socialization of youth in the conditions of transformation of the social and economic relations, crisis situations in various spheres of life of society have been studied in the paper. The socio-economic conditions of modern Russian society defining bachelors’ professional socialization have been investigated. Domestic researches of graduates’ social and professional adaptation have been analyzed. Main difficulties which university graduates meet in the course of professional social adaptation have been revealed. The attention on social institute of professional education exerting a great influence on process of socialization of an individual has been focused. Professional focused training in higher education institution; technologies creating imitating actions during the educational or work practice of students have been presented as a condition of reduction of professional adaptation terms. The authors pay attention to the question of university graduate’s employment which is one of criteria of overall performance on bachelor’s training for modern high school education and, at the same time, starts process of adaptation of a university graduate to modern conditions of labor market which result will be a mastering professional and personal qualities for increase in competitiveness in constantly changing production conditions. The great value to ability to adapt quickly to variability of social living conditions, ability to react flexibly to modern calls in the conditions of work and public life of society have been emphasized.